Predictive costs in medical care for Koreans with metabolic syndrome from 2009 to 2013 based on the National Health Insurance claims dataset - Jeong Seon Yoo; Eun Yeong Choe; Yoo Mee Kim; Se Hwa Kim; Young Jun Won (The Korean Journal of Internal Medicine, 2020)
Background/Aims Although metabolic syndrome has been associated with increasing medical costs worldwide, there have been no studies using a nationwide and longitudinal South Korean dataset. We investigated trends in subsidized medical costs among Korean adults with metabolic syndrome. Methods This study was based on the National Sample Cohort database of South Korea. We used data of national health checkups in 2009 as well as data of subsidized prescription drugs and the Korean Classification of Disease diagnosis codes from claims in 2007 to 2008 to identify underlying diseases. We calculated the direct medical costs, which were subsidized by the Korean National Health Insurance, among 204,768 individuals older than 20 years from 2009 to 2013. Results The proportion of subjects with metabolic syndrome was 27.2%. Direct medical costs for 5 years differed by a magnitude of 2.16 between subjects with and without metabolic syndrome. The costs increased by approximately 41.8% in the metabolic syndrome group in 5 years. Direct medical costs increased with every additional risk factor, even if a subject had less than three risk factors of metabolic syndrome. Metabolic syndrome per se and all of its components, except low serum high-density lipoprotein cholesterol level, resulted in a significant increase in medical costs. Conclusions The medical costs of subjects with metabolic syndrome were higher than that of those without metabolic syndrome and it increased with the number of risk factors. Further research using cumulative data of more than 10 years, including unsubsidized and indirect costs, is needed in the future.